EFEKTIVITAS PEMBERLAKUAN UNDANG-UNDANG NOMOR 28 TAHUN 2009 TERHADAP PAD KABUPATEN SIDOARJO - Choirunnisa, Choirunnisa; Mildawati, Titik (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This research has been conducted in the Department of Revenue, Financial Management and Assets (DPPKA) of Sidoarjo district. The purpose of this research is to find out the contribution of local tax and local retribution to the Local own-sources revenue (PAD), the effectiveness of the enactment of Laws No. 28 of 2009 about the local tax and local retribution (UU PDRD), as well as the efforts of the Department of Revenue, Financial Management and Assets (DPPKA) of Sidoarjo district in order to increase the local tax and local retribution (PDRD) which can support the enhancement of local own-source revenue (PAD). The result of the research shows that the contribution of the local tax to the local own-source revenue is already high whereas the contribution of the local retribution to the local own-source revenue is still low. The effectiveness of local tax and local retribution laws (UU PDRD) experiences enhancement, since the enactment of local tax and local retribution laws (UU PDRD), great authority is given to the local government in the field of local taxation moreover there are 4 additional of new tax types which will be collected by the local government i.e. cigarettes Tax, land and building of rural and urban tax, swallowsâ nest Tax, and fees on the acquisition of rights to land and buildings (BPHTB) so that it will increase the local own-source revenue every years.Keywords: Local Tax, Local Retribution, Local Own-Source Revenue.